Human Peptides α-Defensin-1 and -5 Inhibit Pertussis Toxin - Kling Carolin; Pulliainen Arto T; Barth Holger; Ernst Katharina (MDPI, 2022)
Bordetella pertussis causes the severe childhood disease whooping cough, by releasing several toxins, including pertussis toxin (PT) as a major virulence factor. PT is an AB(5)-type toxin, and consists of the enzymatic A-subunit PTS1 and five B-subunits, which facilitate binding to cells and transport of PTS1 into the cytosol. PTS1 ADP-ribosylates alpha-subunits of inhibitory G-proteins (G alpha i) in the cytosol, which leads to disturbed cAMP signaling. Since PT is crucial for causing severe courses of disease, our aim is to identify new inhibitors against PT, to provide starting points for novel therapeutic approaches. Here, we investigated the effect of human antimicrobial peptides of the defensin family on PT. We demonstrated that PTS1 enzyme activity in vitro was inhibited by alpha-defensin-1 and -5, but not beta-defensin-1. The amount of ADP-ribosylated G alpha i was significantly reduced in PT-treated cells, in the presence of alpha-defensin-1 and -5. Moreover, both alpha-defensins decreased PT-mediated effects on cAMP signaling in the living cell-based interference in the G alpha i-mediated signal transduction (iGIST) assay. Taken together, we identified the human peptides alpha-defensin-1 and -5 as inhibitors of PT activity, suggesting that these human peptides bear potential for developing novel therapeutic strategies against whooping cough.